The classroom relational environment and children's early development in preschool. Issue 4 (14th April 2020) - Nguyen, Tutrang; Ansari, Arya; Pianta, Robert C.; Whittaker, Jessica V.; Vitiello, Virginia E.; Ruzek, Erik
Abstract: The present study considered the ways in which interactional quality in the classroom and teacher–child relationships independently and synergistically shaped the early academic, social‐behavioral, and executive function outcomes of 1, 498 preschoolers from low‐income families from a large, culturally, and linguistically diverse county. The findings revealed that children who had closer and less conflictual relationships with their teachers demonstrated greater improvements in all domains of school readiness across the preschool year. Moreover, preschool attendees did not reap the maximum academic benefits from high quality classroom environments unless they also had high‐quality individual relationships with their teachers. Implications for policy and practice are discussed.